Literate in what? - Sibayan, Bonifacio P. (The RAP Journal, 1991)
The proper questions about literacy/ illiteracy are the following: Literate or illiterate in what language? Literate or illiterate in what subject or topic or what is called in sociolinguistics "register"? Literate or illiterate in what writing system?